Design and application of self-healable polymeric films and coatings for smart food packaging - Wing-Fu Lai (npj Science of Food, 2023)
Abstract Smart packaging materials enable active control of parameters that potentially influence the quality of a packaged food product. One type of these that have attracted extensive interest is self-healable films and coatings, which show the elegant, autonomous crack repairing ability upon the presence of appropriate stimuli. They exhibit increased durability and effectively lengthen the usage lifespan of the package. Over the years, extensive efforts have been paid to the design and development of polymeric materials that show self-healing properties; however, till now most of the discussions focus on the design of self-healable hydrogels. Efforts devoted to delineating related advances in the context of polymeric films and coatings are scant, not to mention works reviewing the use of self-healable polymeric materials for smart food packaging. This article fills this gap by offering a review of not only the major strategies for fabrication of self-healable polymeric films and coatings but also the mechanisms of the self-healing process. It is hoped that this article cannot only provide a snapshot of the recent development of self-healable food packaging materials, but insights into the optimization and design of new polymeric films and coatings with self-healing properties can also be gained for future research.